2021
DOI: 10.2147/dmso.s332416
|View full text |Cite
|
Sign up to set email alerts
|

Latent Autoimmune Diabetes in Adults (LADA) and its Metabolic Characteristics among Yemeni Type 2 Diabetes Mellitus Patients

Abstract: Purpose: Although there is ample data about the prevalence of diabetes in the Middle East, little is known about the prevalence and features of autoimmune diabetes in this region. The aim of this study was to investigate the prevalence and metabolic characteristics of latent autoimmune diabetes in adults (LADA) amongst Yemeni Type 2 DM patients. Patients and Methods: In this cross-section study, 270 Type 2 DM patients aged 30-70 years were recruited from the National Diabetes Center, Al-Thowra Hospital, Sana'a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
(171 reference statements)
1
2
0
Order By: Relevance
“…Of the five ICA-positive patients in this study, three (60%) were female and two (40%) were male, showing no significant difference in ICA prevalence between opposite genders. Our results are consistent with those previously reported by Al-Zubairi et al 5 Similarly, there are other studies showing no significant correlation between patient gender and LADA prevalence. 22,24 Although autoimmune diseases are generally more common in women, 24 some other studies have reported a higher LADA prevalence in men.…”
Section: Various Studies Have Shown That the Prevalence Of Adult-onse...supporting
confidence: 94%
See 2 more Smart Citations
“…Of the five ICA-positive patients in this study, three (60%) were female and two (40%) were male, showing no significant difference in ICA prevalence between opposite genders. Our results are consistent with those previously reported by Al-Zubairi et al 5 Similarly, there are other studies showing no significant correlation between patient gender and LADA prevalence. 22,24 Although autoimmune diseases are generally more common in women, 24 some other studies have reported a higher LADA prevalence in men.…”
Section: Various Studies Have Shown That the Prevalence Of Adult-onse...supporting
confidence: 94%
“…Although glutamic acid decarboxylase autoantibody (GADA), islet cell autoantibody (ICA), insulinoma-associated antigen-2 autoantibody (IA-2), and zinc transporter-8 autoantibody (ZnT8) are the most important markers in prediction and diagnosis of autoimmune type 1 diabetes mellitus (T1DM), some type 2 diabetes mellitus (T2DM) patients can show these autoantibodies just like T1DM patients. [1][2][3] This type of diabetes is known as latent autoimmune diabetes in adults (LADA) 4,5 or adult-onset autoimmune diabetes. [1][2][3][4][5] LADA describe people with slowly progressive insulin-dependent diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation